Mechanism of Bilirubin Diglucuronide Formation in Intact Rats: BILIRUBIN DIGLUCURONIDE FORMATION IN VIVO - Blanckaert, Norbert (1980)
Although it is well established that bilirubin monoglucuronide is formed in the liver from bilirubin by a microsomal bilirubin uridine diphosphate (UDP)-glucuronosyltransferase, the subcellular site of conversion of monoglucuronide to diglucuronide and the molecular mechanism involved in diglucuronide synthesis have not been identified. Based on in vitro studies, it has been proposed that two fundamentally different enzyme systems may be involved in diglucuronide synthesis in rat liver: (a) a microsomal UDP-glucuronosyltransferase system requiring UDP-glucuronic acid as sugar donor or (b) a transglucuronidation mechanism that involves transfer of a glucuronosyl residue from one monoglucuronide molecule to another, catalyzed by a liver plasma membrane enzyme. To clarify the mechanism by which bilirubin monoglucuronide is converted in vivo to diglucuronide, three different experimental approaches were used. First, normal rats were injected with either equal amounts of bilirubin-IIIα [(14)C]monoglucuronide and unlabeled bilirubin-XIIIα monoglucuronide, or bilirubin-XIIIα [(14)C]monoglucuronide and unlabeled bilirubin-IIIα monoglucuronide. Analysis of radiolabeled diglucuronide excreted in bile showed that [(14)C]glucuronosyl residues were not transferred between monoglucuronide molecules. Second, in normal rats infused intravenously with dual-labeled [(3)H]bilirubin [(14)C]monoglucuronide, no transfer or exchange of the [(14)C]glucuronosyl group between injected and endogenously produced bilirubin monoglucuronide could be detected in the excreted bilirubin diglucuronide. Third, in homozygous Gunn rats, injected (14)C-labeled or unlabeled bilirubin mono- or diglucuronides were excreted in bile unchanged (except that diglucuronide was hydrolyzed to a minor degree). This indicates that Gunn rats, which lack bilirubin UDP-glucuronosyltransferase activity, are unable to convert injected monoglucuronide to diglucuronide. Collectively, these findings establish that a transglucuronidation mechanism is not operational in vivo and support the concept that bilirubin diglucuronide is formed by a microsomal UDP-glucuronosyltransferase system.